Privasi, Keamanan dan Niat Memakai Payment Fintech LinkAja pada UMKM Padang - Desiyanti, Rika (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Financial technology has become an opportunity and a problem for the public sector and SMEs or Indonesian micro, small and medium enterprises in recent years, especially those in the city of Padang. This research aims to analyze the effect of privacy and security on the intention to use LinkAja’s payment financial technology. The problem is that fewer people use the LinkAja fintech payment application compared to DANA, GoPay, OVO, and ShopeePay. LinkAja noted that its market share has the smallest transaction value of the total value of e-wallet transactions in IndonesiaPrimary data is needed, and distribute the questionnaire through a google form program. The sampling technique is convenience sampling with a total sample of one hundred and thirty-six respondents. Using the Smart PLS program, this study includes a measurement model assessment (MMA) program, descriptive analysis, and structural model assessment (SMA). Results show that privacy has a positive effect and significance on intentions to use financial payment technology. Security also positively and significantly impacts using monetary payment technology for SMEs’ Padang.